2012
DOI: 10.1016/j.jpha.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive stripping voltammetric methods for determination of aripiprazole

Abstract: Anodic behavior of aripiprazole (ARP) was studied using electrochemical methods. Charge transfer, diffusion and surface coverage coefficients of adsorbed molecules and the number of electrons transferred in electrode mechanisms were calculated for quasi-reversible and adsorption-controlled electrochemical oxidation of ARP at 1.15 V versus Ag/AgCl at pH 4.0 in Britton–Robinson buffer (BR) on glassy carbon electrode. Voltammetric methods for direct determination of ARP in pharmaceutical dosage forms and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A look at the recently published literature shows that reference electrodes with nanoporous glass plugs are not only used frequently for measurements with aqueous samples but are also very popular for measurements in organic solvents such as acetonitrile, 34 propylenecarbonate, 35 methanol, 36 dichloromethane, 37 and ionic liquids. 38 This prompted us to investigate the performance of reference electrodes with nanoporous glass plugs also with acetonitrile as a representative organic solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A look at the recently published literature shows that reference electrodes with nanoporous glass plugs are not only used frequently for measurements with aqueous samples but are also very popular for measurements in organic solvents such as acetonitrile, 34 propylenecarbonate, 35 methanol, 36 dichloromethane, 37 and ionic liquids. 38 This prompted us to investigate the performance of reference electrodes with nanoporous glass plugs also with acetonitrile as a representative organic solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A wide variety of methods are available for the determination of ARP in pharmaceutical preparations and biological samples, such as chromatography, [6][7][8][9][10][11][12][13][14][15][16][17] mass spectrometry, [18][19][20][21][22][23][24][25][26][27] electrophoresis, 28,29 spectrophotometry [30][31][32][33][34][35][36] and electrochemistry. 37,38 Chemiluminescence (CL) is an attractive means of detection because it presents low detection limits, a wide linear working range and uses relatively simple instrumentation. For these reasons, CL has received much attention in various elds, especially in combination with separation methods, for analysis of drugs in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that by increasing the v, the E p shifted to more negative potentials and accompanied with the increase of the I p . The increase of I p indicated an adsorption phenomenon of the RB5 dye at the surface of the mercury electrode [28,29]. A linear relationship was observed between log I p against log v with a slope of 0.5282 (R 2 = 0.9982, n = 6), as shown in Figure 3.…”
Section: Results and Discussion Electrochemical Behaviour Of The Rb5 Dyementioning
confidence: 80%